Analysis of the Level of Work Motivation Related to Nurse Performance” - Tiveni Elisabhet; Robi Awaludin; Ika Purwanto; Andi Sudrajat (Indonesian Journal of Global Health Research, 2025)
Nursing services in hospitals are one of the determining factors in the quality of hospitals in the community, therefore every effort to improve the quality of hospital services must be accompanied by efforts to improve the quality of nursing services. Considering the important role of nurses in carrying out their duties, nurses are required to further improve their abilities and performance and to improve this performance work motivation is needed. This research aims to determine the relationship between work motivation and nurse performance at RSUD dr. Adjidarmo Lebak Banten. This research used a correlational descriptive design with a cross sectional approach with 114 nurse respondents. Data were collected using two questionaires, The Motivation at Work Scale (MAWS) to measure work motivation levels and The Nursing Performance Instrument (NPI) to measure levels of nurse performance, the data are taken at the same time. There is a relationship between work motivation and nurse performance in nurses at RSUD dr. Adjidarmo Lebak Banten, proven by the p-value of 0,003. There is a relationship between work motivation and nurse performance, it is hoped that health service institutions can increase nurses' work motivation as a need for self-actualization, so that it can encourage individuals to carry it out well.